2003
DOI: 10.1104/pp.103.030031
|View full text |Cite
|
Sign up to set email alerts
|

Brassinolide InducesIAA5, IAA19, and DR5, a Synthetic Auxin Response Element in Arabidopsis, Implying a Cross Talk Point of Brassinosteroid and Auxin Signaling

Abstract: Despite numerous physiological studies addressing the interactions between brassinosteroids (BRs) and auxins, little is known about the underlying molecular mechanisms. We studied the expression of IAA5 and IAA19 in response to treatment with indole acetic acid (IAA) or brassinolide (BL), the most active BR. Exogenous IAA induced these genes quickly and transiently, whereas exogenous BL induced them gradually and continuously. We also found that a fusion of DR5, a synthetic auxin response element, with the GUS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
176
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(196 citation statements)
references
References 57 publications
20
176
0
Order By: Relevance
“…1A). As previously reported, response dynamics differed somewhat between the two hormones (Nakamura et al, 2003a). Seedlings treated with the natural auxin indole-3-acetic acid (IAA) sustained a similar level of mRNA induction after 1 or 3 h. For seedlings treated Figure 1.…”
Section: Saur15 Is Induced By Auxin and Brassinosteroid Treatmentmentioning
confidence: 64%
See 2 more Smart Citations
“…1A). As previously reported, response dynamics differed somewhat between the two hormones (Nakamura et al, 2003a). Seedlings treated with the natural auxin indole-3-acetic acid (IAA) sustained a similar level of mRNA induction after 1 or 3 h. For seedlings treated Figure 1.…”
Section: Saur15 Is Induced By Auxin and Brassinosteroid Treatmentmentioning
confidence: 64%
“…Growth promotion by auxin or brassinosteroids requires the function of both signaling pathways (Nakamura et al, 2003a(Nakamura et al, , 2003b(Nakamura et al, , 2006Nemhauser et al, 2004). It is less clear if this phenomenon reflects a convergence at the level of transcriptional control .…”
Section: Saur15 Is Induced By Auxin and Brassinosteroid Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Seventeen to 25% of the auxin-induced genes are also activated by BL in microarray analyses (Goda et al, 2004;Nemhauser et al, 2004). Genes responsive to both auxin and BL include those of early auxin-responsive gene families, such as AUX/IAA, SAUR, and GH3, and a putative transcriptional regulator for tropic responses, MSG2/IAA19 (Tatematsu et al, 2004), also responds to both auxin and BL (Nakamura et al, 2003a). The expression of several genes was found to be synergistically promoted by auxin and BL (Nakamura et al, 2003b;Nemhauser et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The biological evidence, acquired through experiments using reporters such as DR5:GFP, suggests that the canals in fact have high auxin concentrations (65) . Kramer (50) has shown that canals with high flux and high concentration can be formed with the addition of auxin influx transporters that actively pump auxin into cells in the canal from the surrounding apoplast, or efflux transporters that pump auxin out of cells bordering the canal towards the cells of the canal.…”
Section: Venation Patterns and Canalisation Modelsmentioning
confidence: 99%